2014
DOI: 10.1142/s0217751x14300117
|View full text |Cite
|
Sign up to set email alerts
|

Black holes within asymptotic safety

Abstract: Black holes are probably among the most fascinating objects populating our universe. Their characteristic features found within general relativity, encompassing spacetime singularities, event horizons, and black hole thermodynamics, provide a rich testing ground for quantum gravity ideas. We review the status of black holes within a particular proposal for quantum gravity, Weinberg's asymptotic safety program. Starting from a brief survey of the effective average action and scale setting procedures, an improve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 157 publications
(247 reference statements)
9
128
0
Order By: Relevance
“…Moreover, we have found that, for the same value of the classical black hole mass, the event horizon radius (and the BekensteinHawking entropy) decreases when the strength of the scale dependence increases. This is in agreement with the findings in [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we have found that, for the same value of the classical black hole mass, the event horizon radius (and the BekensteinHawking entropy) decreases when the strength of the scale dependence increases. This is in agreement with the findings in [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 93%
“…inflation [28][29][30][31], reheating [32], the cosmological microwave background [33,34], black hole formation [35][36][37] and the vacuum energy density during the evolution of the Universe [38]. As these phenomena are not entirely independent and are deserving of a detailed investigation in their own right, a full study of the early history of the Universe in presence of Higgsplosion is beyond the scope of this work.…”
Section: Phenomenology and The Early Universe With Higgsplosionmentioning
confidence: 99%
“…On this basis, we expect that it is feasible to compute the fingerprints of Asymptotic Safety in the Unruh effect. This may also be relevant for understanding the fate of black holes within Asymptotic Safety [88][89][90][91][92][93][94][95][96][97][98][99] based on first principles.…”
Section: Discussionmentioning
confidence: 99%